2019
DOI: 10.1302/2046-3758.812.bjr-2019-0038.r1
|View full text |Cite
|
Sign up to set email alerts
|

Does a high-fat diet affect the development and progression of osteoarthritis in mice? A systematic review

Abstract: Aims The aim of this study was to systematically review the literature for evidence of the effect of a high-fat diet (HFD) on the onset or progression of osteoarthritis (OA) in mice. Methods A literature search was performed in PubMed, Embase, Web of Science, and Scopus to find all studies on mice investigating the effects of HFD or Western-type diet on OA when compared with a control diet (CD). The primary outcome was the determination of cartilage loss and alteration. Secondary outcomes regarding local and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Data showed that the BMD of rats with intermittent unloading was comparable with that of normal controls, while being significantly greater than that of rats with full-time suspension (Supplementary Figure c). In addition, weight and obesity are important risk factors during the development of OA, 34 and our data reveal that the weight of rats was comparable among the three groups at the endpoint of the experiment (Supplementary Figure d).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Data showed that the BMD of rats with intermittent unloading was comparable with that of normal controls, while being significantly greater than that of rats with full-time suspension (Supplementary Figure c). In addition, weight and obesity are important risk factors during the development of OA, 34 and our data reveal that the weight of rats was comparable among the three groups at the endpoint of the experiment (Supplementary Figure d).…”
Section: Discussionsupporting
confidence: 51%
“…On the other hand, inflammatory cytokines brought about by diet or injuries are also intensively involved in joint destruction in OA. 14 , 34 Among them, IL-1β is an important cytokine participant in catabolism and degeneration of cartilage during OA development. 13 , 35 IL-1β can not only increase the expression and activation of MMPs, 36 but also accelerate the breakdown of collagen II and proteoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that while previous studies revealed unequivocally that HFD caused exacerbation of PTOA, inconsistent results have been observed in regard to the ability of HFD in OA induction in mouse models [195].…”
Section: Obesity-induced Oa Modelsmentioning
confidence: 91%
“…Higher OA incidence in obese people is attributed to not only excessive joint loading caused by increased body weight, but also the associated systemic inflammation, dysregulated lipid metabolism, and altered adipokine profile [193,194]. Mice fed with a high-fat diet (HFD) exhibit higher levels of proinflammatory cytokines, including IL-1β, IL-6, IL-8, IL-13, leptin, and TNF-α; also present at higher levels in these mice are proteins involved in cartilage metabolism, such as TGF-β1, MMP-13, and vascular endothelial growth factor-α (VEGF-α) [195].…”
Section: Obesity-induced Oa Modelsmentioning
confidence: 99%
See 1 more Smart Citation